Pengembangan Literasi dan Numerasi melalui Kampus Mengajar Angkatan 2 di SD Inpres Paga - Jessi Claudia Boe (Prima Abdika: Jurnal Pengabdian Masyarakat, 2023)
Teaching Campus Batch 2 is one of Merdeka Campus' policies on the type of teaching activities in schools. This program invites students to  contribute  directly  to  the education  of  elementary  and  junior high school students in schools throughout Indonesia, especially in the 3 T areas (lagging, outermost, and leading). The Teaching Campus Program Batch  2, especially  at the Paga Inpres Elementary School, has been going on for 5 months, from August to December 2021. The activities carried out are Knowledge Transfer, Technology Transfer and Administrative Affairs. The method used in this study is the method of habituation in the sense that students  can  develop literacy  and numeracy  in the  elementary  school.  The  final  result  in this study is  that  students  can  develop  literacy  and  numeracy  with  activities  that  Campus  Teaching students have done at Paga Inpres Elementary School.